Design and Psychometric Properties of a Self-Care Questionnaire for the Elderly - Masomeh Hemmati Maslak Pak; Leila Hashemlo (University of Social Welfare & Rehabilitation Sciences, 2015)
Objectives: The purpose of this study was to design an Iranian cultural adaptable questionnaire for the assessment of self-care in the elderly. Methods & Materials: This methodological study was conducted in 2 phases. In the first phase, items and primary categories of the new instrument were identified from the review of the studies based on Orem’s theory. In the second phase, the psychometric properties of the instrument such as face validity, content validity, construct validity, and internal consistency were determined. In this phase, 225 elderly people in Uremia City, Iran were randomly selected from nursing homes and the Elderly Center of Uremia to participate in the study. Results: Forty-five items of the questionnaire were identified from the review of the studies based on Orem’s theory. After determining face and content validity in qualitative and quantitative terms, the questionnaire items reduced to 40. The results of the exploratory factor analysis on the questionnaire indicated the existence of 5 factors. These 5 factors explained nearly 79.93% of the variance of the questionnaire. Also, the internal consistency (Cronbach α) was 0.864. Conclusion: Based on the results, we concluded that the assessment self-care questionnaire for the elderly with 40 items appears to be a promising tool and provides reliable and valid data helping to determine elderly self-care in different settings such as clinical setting and research environments by health care providers.